Faktor Dominan Keluhan Low Back Pain (LBP) pada Truck Drivers Kota Palembang - ARIE ANGGARA; Novrikasari Novrikasari; Yuanita Windusari (Jurnal Tekno Global, 2026)
ABSTRACT Low Back Pain (LBP) is one of the most common musculoskeletal disorders with a high prevalence among truck drivers. LBP is a leading cause of activity limitations, disability, inability to work, and work absenteeism. This study aims to analyze the dominant factors of LBP complaints among truck drivers of the Environmental Service (DLH) in Palembang City. A cross-sectional approach was employed in this study. The respondents were truck drivers in Palembang City. A total of 107 drivers were selected using a non-probability purposive sampling technique. The results showed that 65 respondents (60.7%) experienced LBP complaints. The majority of the drivers, 96 respondents (89.7%), did not use Lumbar Support while driving. The use of Lumbar Support was found to be the dominant occupational factor associated with LBP complaints among truck drivers (Prevalence Ratio = 16.565). It is recommended that drivers consistently use Lumbar Support while driving as a preventive measure to reduce the risk of LBP complaints among truck drivers in Palembang City. Keywords : Musculoskeletal Disorders, Low Back Pain, Drivers, Truck     ABSTRAK Low Back Pain (LBP) merupakan salah satu gangguan muskuloskeletal dengan intensitas tertinggi pada truck drivers. LBP merupakan salah satu penyebab utama keterbatasan aktivitas, kecacatan, ketidakmampuan untuk bekerja, dan ketidakhadiran dalam bekerja. Tujuan penelitian ini untuk menganalisis Faktor Dominan keluhan LBP pada truck drivers Kota Palembang. Metode yang digunakan dengan pendekatan cross-sectional. Responden dalam penelitian ini adalah truck drivers Kota Palembang. Sampel dalam penelitian ini sebanyak 107 drivers yang diambil dengan teknik sampling nonprobability dengan cara purposive sampling. Hasil penelitian menunjukkan sebanyak 65 responden (60,7%) mengalami keluhan LBP pada drivers. Mayoritas sebanyak 96 responden (89,7%) tidak menggunakan Lumbar Support pada saat mengemudi. Penggunaan Lumbar Support merupakan variabel dominan terkait faktor pekerjaan dengan keluhan LBP pada truck drivers Kota Palembang (PR = 16,565). Drivers diharapkan selalu menggunakan Lumbar Support selama mengemudi hal ini dimaksudkan untuk mencegah keluhan LBP pada truck drivers Kota Palembang. Kata Kunci : Musculoskeletal Disorders, Low Back Pain, Drivers, Truk